Urban Health Data in India: Mapping Gaps & Solutions - Kumar, Vibhor; Deshmukh, Ashwin (Journal of Urban Health Research, 2023)
Inadequacies of current health information systems in capturing the diverse health needs and vulnerabilities within urban populations, emphasizing the need to move beyond fragmented traditional data collection approaches. By incorporating emerging technologies and enhancing governance structures, such as strengthening coordination mechanisms and promoting transparency, urban health stakeholders can overcome data gaps and better address the evolving health landscape. Keywords: urban health - urban health data - digital health - health systems